A security enhanced timestamp-based password authentication scheme using smart cards - Pathan, Al-Sakib Khan; Hong, Choong Seon (The Institute of Electronics, Information and Communication Engineers, Japan, 2007)
The intent of this letter is to propose an efficient timestamp based password authentication scheme using smart cards. We show various types of forgery attacks against Shen et al.’s timestamp-based password authentication scheme and improve their scheme to ensure robust security for the remote authentication process, keeping all the advantages of their scheme. Our scheme successfully defends the attacks that could be launched against other related previous schemes.